2019
DOI: 10.1002/adma.201902542
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Modification of the Tumor Cell Surface with Immunomodulating Nanoparticles for Effective Suppression of Tumor Growth in Mice

Abstract: Current cancer immunotherapies including chimeric antigen receptor (CAR)-based therapies and checkpoint immune inhibitors have demonstrated significant clinical success, but always suffer from immunotoxicity and autoimmune disease. Recently, nanomaterial-based immunotherapies are developed to precisely control in vivo immune activation in tumor tissues for reducing immune-related adverse events. However, little consideration has been put on the spatial modulation of interactions between immune cells and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Two recent studies demonstrate that tumors can be coated with antibodies and antibody Fc fragments, exposing them to NK cell-mediated ADCC. These studies take advantage of specific biochemical characteristics of the TME, such as lower pH levels and high sialic acid expression, to directly coat tumors with antibody fragments (300,301). Subsequently, NK cells can recognize these Fc IgG fragments and become activated in-situ to promote tumor clearance in in-vivo models.…”
Section: Turning "Cold" Tumors "Hot" For Nk Cell Immune Surveillance mentioning
confidence: 99%
“…Two recent studies demonstrate that tumors can be coated with antibodies and antibody Fc fragments, exposing them to NK cell-mediated ADCC. These studies take advantage of specific biochemical characteristics of the TME, such as lower pH levels and high sialic acid expression, to directly coat tumors with antibody fragments (300,301). Subsequently, NK cells can recognize these Fc IgG fragments and become activated in-situ to promote tumor clearance in in-vivo models.…”
Section: Turning "Cold" Tumors "Hot" For Nk Cell Immune Surveillance mentioning
confidence: 99%
“…Cellular backpacks using nanoparticles without being internalized also hold promise of targeted drug delivery and enhanced cancer immunotherapy, which integrates the respective merits of nanoparticles as drug depots and cells with natural directional migration potency as active carriage 143, 144. Huang et al reported nanoparticle-conjugated T cells for enhanced targeting of chemotherapeutics to disseminated tumor cells in lymph nodes 145.…”
Section: Engineering Cells Via Chemical Bioconjugationmentioning
confidence: 99%
“…In addition, a nondegradable CT‐CPNC was also designed to facilitate the recognition of tumor cells by natural killer (NK) cells to trigger antibody‐dependent cell‐mediated cytotoxicity for cancer immunotherapy. [ 55 ]…”
Section: Structures and Physicochemical Propertiesmentioning
confidence: 99%